(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Solar thermal collector systems allow solar energy to be used for cooling and heating. A heat transfer fluid is utilized in these collectors to transmit collected solar energy to applications that need it. Scientists have proposed various collector designs and better collection materials to enhance the solar collector’s conversion efficiency. The use of Nano fluids to study solar collectors utilizing evacuated tubes is discussed in this article. The researchers used a two-step method to prepare Nano fluids, which improved nano fluid stability. Swasco laboratories in Mumbai provided the nanoparticles. Nanoparticles were mixed in distilled water and well blended before being used in the heat pipes. In this work, the Nano fluids were made in two stages, which enhanced nano fluid stability. Before being put in the heat tubing, the nanoparticle was well mixed with distilled water. Most solar collectors may be able to enhance their overall performance by using nano fluids. However, unless a few issues about nano fluid stability, overall performance, and hysteresis expectedness are addressed, the full potential of Nano fluids in heat transfer applications will not be realized.